PENGARUH LINGKUNGAN KAMPUS STIE MUARA TEWEH TERHADAP KESEJAHTERAAN MENTAL MAHASISWA - Nor Arapah; Dwi Susila Kartini (JURNAL ILMU EKONOMI (MANAJEMEN PERUSAHAAN) DAN BISNIS, 2026)
The purpose of this study is to examine and analyze the influence of the Physical Campus Environment, Social Campus Environment, and Academic Campus Environment on Students’ Mental Well-Being at STIE Muara Teweh, both simultaneously and partially, as well as to identify the most dominant campus environment variable affecting students’ mental well-being. This study employs a quantitative research approach with active students of STIE Muara Teweh as the research subjects. The population of this study consists of 100 students, all of whom were used as the research sample through a saturated sampling (census) technique. Data were collected through questionnaires using a Likert scale and literature study. The data analysis techniques include validity testing, reliability testing, classical assumption testing, and multiple linear regression analysis, processed using SPSS version 26 for Windows. The results of the study indicate that the Physical Campus Environment, Social Campus Environment, and Academic Campus Environment simultaneously have a significant effect on Students’ Mental Well-Being. Partially, all three variables also show a significant effect on students’ mental well-being at STIE Muara Teweh. Based on the results of the Standardized Coefficients Beta test, the Social Campus Environment (X₂) is identified as the most dominant variable influencing students’ mental well-being compared to the other variables.